PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 033 SINTONG - ', Hamdani; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Background of this research by the low results of social studies class III Sintong SDN 033, with an average grade 65.28. While the value of minimum completeness criteria (KKM) IPA is 70. Of the 18 students who completed only 6 people, while 12 others were incomplete. This study aims to improve learning outcomes IPS Class III students of SDN 033 Sintong. This research is the Classroom Action Research (CAR) conducted by two cycles and twice daily test (replications end of the cycle) to implement cooperative learning model NHT. The subjects were students of class III Elementary School Sintong 033, with the number of students as many as 18 people. Data collection instruments used were observation sheet activities of teacher and student activity and learning about the test results. Based on the analysis of research data after learning corrective action on the first cycle increased the average value of students increased to 69.44. In the second cycle increased again with the average value becomes 73.89. Activities teachers in the learning process also increased from 53.33% increase to 83.33% at the end of the cycle two. The increased activity of teachers also have an impact on student activity from data analysis activities of students in the first cycle the first meeting of 62.50% increased in the second meeting of the two cycles to 83.33%. Thus the results of this study indicate that the hypothesis is proven.Key Words: Cooperative NHT, learning outcomes IPS